Investigation of lignin peroxidase (LiP) produciton from fungi grown on liquid culture medium - Giap, Vu Dinh; Thu QUynh, Dang; Huu Nghi, Do (Vietnam Journal of Biotechnology, 2021)
Fungi are known to be capable of biosynthesizing various enzymes such as extracellular hydrolytic enzymes and oxydizing to effectively attack lignocellulose structures in the plant cell wall. Lignin peroxidase (LiP) is an extracellular enzyme biosynthesized in a variety of fungi and first isolated in 1987 from P. chrysosporium. The LiP enzyme is capable of oxydizing compounds with high redox potential (aromatic ring polymers) in the presence of H2O2 resulting in electron oxydation of various compounds including phenols, aromatic amines. Therefore, LiP is an important component of the extracellular enzyme system for lignocellulose degradation. Through polymerization, phenolic compounds reduced reactivity and solubility to be precipitated, thereby reducing toxycity. Therefore, LiP is applied in wastewater cleaning in wastwater containing high phenol content and halogenated phenol toxyns, that are the hydroxyl phenolic compounds. In this study, 39 fungal strains isolated from two ecological regions (Cuc Phuong National Park in Ninh Binh and Muong Phang inDien Bien provinces) were screened for LiP enzyme production. In which, 14 strains grew on a straw substrate medium exhibiting LiP activity with the level ranging from 13.8 to 108.8 U/mL. The LiP of Lentinus squarrosulus MPN 12 identified by molecular analysis exhibited the highest activity as 108 U/mL on basic culture medium and 896 U/mL in optimal culture medium, that was basic medium supplemented with an inducer veratryl alcohol (0.3 g/L), sucrose (10 g/L), urea (5 g/L) for 9 days fermentation at 28 °C, pH 5.0 and 200 rpm. This strain has a high potential for the production of LiP enzyme to convert lignocellulose material.